Tourism Potential of Uzbekistan - Muhsina Juraboyeva (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Abstract: This article provides an in-depth analysis of Uzbekistan’s tourism potential within the context of global travel trends and the nation’s transition towards a diversified, innovation-driven economy. It explores the historical, cultural, and natural assets that form the foundation of Uzbekistan’s competitive advantage in tourism and evaluates the government’s strategic initiatives aimed at transforming the country into a regional hub for sustainable and cultural tourism. The study also investigates the institutional reforms, infrastructure modernisation, and international cooperation that underpin the development of Uzbekistan’s tourism industry in alignment with the United Nations Sustainable Development Goals (SDGs).